ПУҚАРАЛЫҚ ЖӘМИЙЕТИ РАЎАЖЛАНЫЎЫНДА МИЛЛИЙ ҮРП-ӘДЕТ ҲӘМ ДӘСТҮРЛЕРДИҢ РОЛИ - Шерниязова, Г. (SCIENCE and SOCIETY, 2019)
The article presents thoughts about the role of national traditions and customs in the development of civil society. Signs of civil society were primarily associated with the history of the people, their culture, language, customs, and other branches of cultural life. Samples of the culture of Zeroostrism have made a significant contribution to the development of civil society.
Keywords: civil society; social attitude; person; social institute; zoroastrizm; national customs and traditions; national education